2002
DOI: 10.1007/s003800200034
|View full text |Cite
|
Sign up to set email alerts
|

Native valve endocarditis due to Pichia ohmeri

Abstract: Candida species can cause clinical manifestations in various organs of the cardiovascular system, i.e., the pericardium, myocardium, and endocardium, with endocarditis being the best-known clinical entity. Endocarditis is seen primarily in intravenous drug users and in individuals with damaged native valves, especially in congenital heart disease or rheumatic valvular diseases, and in prosthetic heart valves. The authors present a case of Pichia ohmeri endocarditis in an intravenous drug user, with an unusual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…No additional studies were found during the hand‐screening of the included articles' references. Finally, 35 met the present study's inclusion criteria 3,4,7–39 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…No additional studies were found during the hand‐screening of the included articles' references. Finally, 35 met the present study's inclusion criteria 3,4,7–39 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, K. ohmeri was established as one of the important fungi causing invasive infections in humans [8] . Sepsis or fungemia [4] , [5] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , catheter-related blood stream infection [10] , [17] , phlebitis [9] , peritonitis [19] , and endocarditis [14] , [16] have been reported. Diabetes mellitus, malignant tumor, prosthetic heart valves, and chronic kidney diseases are considered to be risk factors for invasive infections due to K. ohmeri .…”
Section: Discussionmentioning
confidence: 99%
“…Pichia ohmeri , a teleomorphic form of Candida guilliermondii , is an environmental strain 9 used commonly in the food industry for fermentation of pickles, rinds, and fruit. Its first clinical isolation was made in the pleural fluid of a patient in whom the fungus was considered a contaminant 10 or a harmless coloniser.…”
Section: Discussionmentioning
confidence: 99%
“…Pichia ohmeri fungaemia of an intravenous drug user, the first case of P. ohmeri prosthetic valve endocarditis in an immunocompetent man, and the first case of urinary tract infection due to this fungus, and P. ohmeri fungaemia related to central venous catheter were reported. All these cases were successfully treated with amphotericin B and fluconazole 9,14–16 . In 2003, Shin et al.…”
Section: Discussionmentioning
confidence: 99%